Cloning of the Arabidopsis WIGGUM gene identifies a role for farnesylation in meristem development - Ziegelhoffer, Eva C. (The National Academy of Sciences, 2000)
Control of cellular proliferation in plant meristems is important for maintaining the correct number and position of developing organs. One of the genes identified in the control of floral and apical meristem size and floral organ number in Arabidopsis thaliana is WIGGUM. In wiggum mutants, one of the most striking phenotypes is an increase in floral organ number, particularly in the sepals and petals, correlating with an increase in the width of young floral meristems. Additional phenotypes include reduced and delayed germination, delayed flowering, maturation, and senescence, decreased internode elongation, shortened roots, aberrant phyllotaxy of flowers, aberrant sepal development, floral buds that open precociously, and occasional apical meristem fasciation. As a first step in determining a molecular function for WIGGUM, we used positional cloning to identify the gene. DNA sequencing revealed that WIGGUM is identical to ERA1 (enhanced response to abscisic acid), a previously identified farnesyltransferase β-subunit gene of Arabidopsis. This finding provides a link between protein modification by farnesylation and the control of meristem size. Using in situ hybridization, we examined the expression of ERA1 throughout development and found it to be nearly ubiquitous. This extensive expression domain is consistent with the pleiotropic nature of wiggum mutants and highlights a broad utility for farnesylation in plant growth and development.